2005
DOI: 10.1007/s00572-004-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizal fungi and kinetin on the response of mungbean plants to irrigation with seawater

Abstract: Increasing use of saline water in irrigation can markedly change the physical and chemical properties of soil. An experiment was carried out to investigate the interaction between the mycorrhizal fungus Glomus clarum, isolated from a saline soil, and kinetin on the growth and physiology of mungbean plants irrigated with different dilutions of seawater (0, 10, 20, and 30%). The growth, chlorophyll concentration and sugar content of mycorrhizal plants was greater than that of non-mycorrhizal plants under all con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
35
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 20 publications
10
35
1
7
Order By: Relevance
“…Higher K + accumulation by inoculated plants in saline soil could be beneficial by maintaining a high K + /Na + ratio and by influencing the ionic balance of the cytoplasm or Na + efflux from plants (Giri et al, 2007;Aleman et al, 2009). Improved ionic ratios in the aerial parts of inoculated-stressed plants have been reported earlier by Giri et al (2003); Rabie (2005); Rabie and Almadini (2005).…”
Section: Discussionsupporting
confidence: 72%
“…Higher K + accumulation by inoculated plants in saline soil could be beneficial by maintaining a high K + /Na + ratio and by influencing the ionic balance of the cytoplasm or Na + efflux from plants (Giri et al, 2007;Aleman et al, 2009). Improved ionic ratios in the aerial parts of inoculated-stressed plants have been reported earlier by Giri et al (2003); Rabie (2005); Rabie and Almadini (2005).…”
Section: Discussionsupporting
confidence: 72%
“…This finding might also be due to the positive effects of AM fungi on plant growth and nutrient acquisition as reported in other AM fungi-inoculated plants grown under saline stress (Giri and Mukerjii 2004;Rabie 2005). In another study, higher chlorophyll contents were reported in mycorrhizal zucchini plants grown under Effects of plant genotype (G: nontransgenic or mangrin transgenic), treatment (T: tap water or 200 mM NaCl), and both interactions.…”
mentioning
confidence: 51%
“…A atividade nitrogenase de nódulos de plantas crescendo nas doses de 500 e 1.000 mg dm -3 Pb foi maior em plantas micorrizadas que em não micorrizadas (Figura 6). Semelhantemente ao observado por Balestrasse et al (2003) em plantas de soja sob estresse por Cd, aquelas não micorrizadas apresentaram pequena redução na atividade da nitrogenase, evidenciando que diferentes MPs podem causar efeito negativo sobre a fixação biológica de N. Como demonstrado por Rabie (2005b) em plantas de Vigna radiata sob condições de estresse salino e por Frason et al (1991) em plantas de soja sob estresse hídrico, a micorrização estimulou a atividade da nitrogenase nessas plantas. Frason et al (1991) sugerem que plantas micorrizadas sob condições de estresse abiótico podem apresentar melhor desempenho na fixação de N 2 em função, possivelmente, do maior suprimento de P fornecido aos nódulos pela associação com FMAs, uma vez que o processo de fixação de N 2 tem alta demanda de energia.…”
Section: Utilização De Formas De Nitrogêniounclassified